Longitudinal analysis of Socioecological obesogenic factors in a National Sample of U.S. children - TaeEung Kim; Junhye Kwon; Chung Gun Lee; Chang-Yong Jang (BMC, 2020)
Abstract Background Childhood obesity is a serious public health threat. Although many researchers conducted research on socioecological determinants of childhood obesity, their longitudinal effects remain inconclusive especially among young children. This study examined socioecological factors and associated transitions of children's body mass index (BMI) status throughout children's kindergarten to elementary school years, using data from a national longitudinal sample. Methods The baseline sample of this study included 1264 children (weighted N = 379,297) extracted from the Early Childhood Longitudinal Study (baseline mean age: 5.24 years). The socioecological framework guided selection of socioecological obesogenic variables (e.g., family activity and parental involvement). Longitudinal ordered logistic regressions were performed to determine the associations between socioecological obesogenic variables and unhealthy/healthy changes in BMI status that captured transitions between healthy and unhealthy weight status (i.e., overweight, obesity, and severe obesity). Results Children with Hispanic ethnicity and nonwhite, less socioeconomic and environmental support, and living in households with fewer family members were more likely than their counterparts to have unhealthy BMI status changes over time (all ps < 0.05). Over the study period, girls were less likely than boys to experience transitions to unhealthy BMI status (all ps < 0.05). Conclusion As hypothesized a priori, the findings of the current affirmed multiple dimensions of how sociological obesogenic factors may influence children's BMI status changes in a longitudinal setting. In order to maintain children's long-term healthy weight, more attention should be paid to socioeconomic obesogenic factors surrounding children as well as individual determinants of obesity (e.g., being physically active and having well-balanced nutrition).